2010
DOI: 10.1159/000303048
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Electrophysiological and Antiarrhythmic Effects of <i>N</i>-n-butyl Haloperidol Iodide

Abstract: Aims: N-n-butyl haloperidol (F2), a novel compound of quaternary ammonium salt derivatives of haloperidol, was reported to antagonize myocardial ischemia/reperfusion injuries. The antiarrhythmic potential and electrophysiological effects of F2 on rat cardiac tissues were investigated. Methods and Results: In Langendorff-perfused rat hearts, the ventricular arrhythmias were induced by left anterior descending coronary artery of rat heart ligated for 20 min before the release of the ligatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
2
11
0
1
Order By: Relevance
“…Calcium overload and calcium transient alterations during ischemia play causal roles in the genesis of arrhythmias [31,32]. Our results indicated that F 2 could reduce the change in calcium transients caused by hypoxia, which may be related to antiarrhythmic properties in ischemia-and reperfusioninduced arrhythmias we found previously [7]. Ca 2+ transients is considered the summation of many microscopic Ca 2+ release events triggered by one or more single Ca 2+ currents [33].…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Calcium overload and calcium transient alterations during ischemia play causal roles in the genesis of arrhythmias [31,32]. Our results indicated that F 2 could reduce the change in calcium transients caused by hypoxia, which may be related to antiarrhythmic properties in ischemia-and reperfusioninduced arrhythmias we found previously [7]. Ca 2+ transients is considered the summation of many microscopic Ca 2+ release events triggered by one or more single Ca 2+ currents [33].…”
Section: Discussionsupporting
confidence: 63%
“…Consistent with previous findings [17,26], we confirmed the series of changes occurring in calcium tran- sients during hypoxia/ischemia, which include an increase in RT25-75 and DT75-25 of Ca 2+ transients, accompanied by the amplitude reducing and increasing of basal Ca 2+ level of calcium transients during 30-min hypoxia. Previous studies showed that F 2 is an L-type calcium channel blocker that inhibited I Ca, L in rat ventricular myocytes [7,8]. In this study on the effects of F 2 on calcium transients and related factors during hypoxia/ ischemia, we found the amplitude of calcium transients reduced during 30-min hypoxia, which could be partly inhibited by F 2 .…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations